2014
DOI: 10.1589/jpts.26.1933
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glucose, TNF-α and IL-6 Blood Levels in Middle-aged Women Associated with Aerobic Exercise and Meditation Training

Abstract: [Purpose] The purpose of this study was to investigate the effects of exercise therapy on glucose, TNF-α and IL-6 blood levels in middle-aged women. [Subjects] A total of 46 participants were assigned to four groups: Type D personality+Exercise (n=12), Type D+no-Exercise (n=12), not-Type D+Exercise (n=12), and not-Type D+no-Exercise (n=10). [Methods] Blood glucose was measured by the hexokinase method. An enzyme-linked immunosorbent assay (ELISA) was used to measure the circulating plasma levels of TNF-α and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(31 reference statements)
1
10
0
Order By: Relevance
“… 23 Another study about mindfulness-based stress reduction reported a continued reduction in Th1 (pro-inflammatory) cytokines over one year of pre-post intervention follow-up. 24 The report that TNF-α showed a significant lower level in the not-Type D personality+Exercise group 25 is similar to our result. The increase of IL-10 (anti-inflammatory cytokine) with the decreased tendency of TNF-alpha and IL-6 (pro-inflammatory cytokines) is a new finding beyond the previous results.…”
Section: Discussionsupporting
confidence: 91%
“… 23 Another study about mindfulness-based stress reduction reported a continued reduction in Th1 (pro-inflammatory) cytokines over one year of pre-post intervention follow-up. 24 The report that TNF-α showed a significant lower level in the not-Type D personality+Exercise group 25 is similar to our result. The increase of IL-10 (anti-inflammatory cytokine) with the decreased tendency of TNF-alpha and IL-6 (pro-inflammatory cytokines) is a new finding beyond the previous results.…”
Section: Discussionsupporting
confidence: 91%
“…Also a recent study of Hur et al (2014) showed that Type D personality was independently associated with significant immune activation and increased levels of TNF-α activity. Our results expand these findings, by analyzing multiple inflammatory biomarkers and combining them into predefined clusters of conceptually related biomarkers (Heringa et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Exercise training produces changes in the concentration of several biologically active molecules including cortisol and testosterone 49 , 50 , 51 ) , which play pivotal roles as catabolic and anabolic agents in gluconeogenesis via the proteolytic pathway. The storage of glycogen and muscular protein synthesis is stimulated by testosterone 52 ) .…”
Section: Discussionmentioning
confidence: 99%